Návrh projektu rekonstrukce domu s podporou MS Project - Horák, Filip (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Bakalářská práce se věnuje problematice projektového řízení, konkrétně využití metod síťové analýzy při řízení projektů. V praktické části je popsán návrh alternativního řešení řízení projektu, konkrétně rekonstrukce domu bytového družstva Radlas 16. Hlavním cílem družstva je dostat budovu do stavu komfortnějšího bydlení a rozšířit dům o půdní vestavbu.

The bachelor thesis deals with the project management issues, specifically the application of flow network analysis in project management. The proposition of alternate is solution of initial project for the housing cooperatives Radlas 16, specifically reconstruction of the house. The main objective of the cooperative is to get the building to the state housing more comfortable and extend the building of the attic.
Proposal of Reconstruction of the House with Support of MS Project
Keywords: Projektové řízení; projekt; časová analýza; síťová analýza; náklady; rizika; Project management; project; time analysis; network analysis; costs; risks